Governing Electronically - Henman, P. author. aut Link
XII, 271 p. 1 illus.
Keywords: This book provides rare insights into the nature of contemporary, technologically-facilitated government. Its multidisciplinary approach demonstrates that information technology is more than a tool for politicians and policy-makers. E-government has reconfigured public administration, policy, power and citizenship.